1980
DOI: 10.1113/jphysiol.1980.sp013095
|View full text |Cite
|
Sign up to set email alerts
|

Irreverisble differential block of A‐ and C‐fibres following local nerve heating in the cat.

Abstract: SUMMARY1. Local heating of a nerve was used to block conduction in the myelinated or A-fibres while preserving normal function in most of the non-myelinated or Cfibres. Compound action potentials of A-and C-fibres, and impulses in single Cfibres were recorded to measure the block.2. Most experiments were done on the posterior tibial nerve of the cat's hind limb. Conducted heat was applied in successive periods of about 2 min each to 15 mm of the exposed nerve..3. The range of temperatures used was between 45 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
2
14
0
2
Order By: Relevance
“…3) could reflect different experimental methods. The length of the heated nerve was 15 mm in the previous study (Klumpp and Zimmermann 1980) but was only 9 mm in our study. In addition, a recent study in rats showed that the sciatic nerve could be blocked by increasing local temperature about 9°C from room temperature using very focused (Ͻ0.1 mm) infrared laser (Duke et al 2013).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…3) could reflect different experimental methods. The length of the heated nerve was 15 mm in the previous study (Klumpp and Zimmermann 1980) but was only 9 mm in our study. In addition, a recent study in rats showed that the sciatic nerve could be blocked by increasing local temperature about 9°C from room temperature using very focused (Ͻ0.1 mm) infrared laser (Duke et al 2013).…”
Section: Discussionmentioning
confidence: 67%
“…7). In addition, these heating durations are only ϳ10% of the durations required to produce a nonreversible nerve block (Klumpp and Zimmermann 1980). However, the safety for repeated application of the short duration heating will still need to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations